Peningkatan Pertumbuhan Mentimun Varietas F1 Semi Baby Merk Bintang Asia dengan Pupuk Organik Cair dari Mikrorganisme Lokal (MOL) Terasi Udang - Listari, Nening; Wijayadi, Ahmad (Jurnal Ilmiah IKIP Mataram, 2023)
Vegetables are a form of product that does not last long, so they are very desirable if they are fresh, for example baby cucumbers which are currently widely cultivated in Indonesia. In West Nusa Tenggara, especially the island of Lombok, it is a vegetable gathering point which is a place for delivering farmers’ crops. Baby cucumbers are very popular with the people in Lombok, therefore the demand for market participants for baby cucumber stocks is very high, while the supply of baby cucumbers from farmers is unpredictable and of course there are many factors that affect production results. This study aims to determine the increase in growth of cucumber variety F1 semi baby star Asia with liquid organic fertilizer with local microorganisms (MOL) from shrimp paste. The use of liquid organic fertilizer MOL shrimp paste to determine the increase in the growth of baby cucumbers as seen from the variables of tendril length, flowering age, fruit length, fruit diameter, fruit weight per plant, and the number of fruit produced. The research used was a Randomized Block Design (RAK) with 5 (five) treatment designs and 3 (three) replications. The number of plants studied in the experiment were 3 sample plants. The treatments studied were the concentration of liquid organic fertilizer, namely P0 = Without liquid organic fertilizer (Control), P1 = 5 ml of liquid organic fertilizer/ l of air, P2 = 10 ml of liquid organic fertilizer/ l of air, P3 = 15 ml of liquid organic fertilizer/ l air, P4 = 20 ml of liquid organic fertilizer/ l of air. The changes observed were tendril length (cm), flowering age (days), fruit length (cm), fruit diameter (cm), fruit weight per plant (kg) and number of fruit planted (fruit). Based on the results of the research conducted, it can be said that the treatment with P3 (15 ml of organic fertilizer) gave better results for 33 days of flowering age, 10.4 cm of fruit length, 3.5 cm of diameter, 2.9 kg of fruit weight. , and the number of fruit per plant 12 pieces. As for the length of the longest baby cucumber tendrils at the time of P4 treatment (20 ml of liquid organic fertilizer / l of water).